A High Performance Terahertz Photoconductive Antenna Array Detector With High Synthesis Efficiency - Shi, Wei; Wang, Zhiquan; Hou, Lei; Wang, Haiqing; Wu, Meilin; Li, Chaofan (Frontiers in Physics, 2021)
A 2×2 terahertz photoconductive antenna (PCA) array detector with high efficiency synthesis characteristic that improves the signal-to-noise ratio (SNR) of the output signals has been reported in this paper. Through micromachining of the substrate material, the current signal generated by the adjacent antenna elements as opposed to that generated by the gap is eliminated. Experiments show that the amplitude of the current signal output by the PCA array detector is consistent with the amplitude of the synchronous superposition of the current signals output by antenna elements, and the detector achieves 93.7% synthesis efficiency. At the same time, the antenna array has low current noise. The highest SNR of the detector is 62dB under the excitation of different light energy, which is related to the number of antenna array elements.